PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE DI BEI TAHUN 2017-2019 - Fajar Aribowo (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
Abstract This study aims to determine: (1) whether profitability is significant on stock prices in property and real estate companies on the IDX in 2017-2019 (2) what is the capital structure is significant on stock prices in property and real estate companies on the IDX in 2017-2019 (3) whether profitability and capital structure have a simultaneous effect on stock prices in property and real estate companies on the IDX in 2017-2019. The data used is secondary data and the sample is in the form of financial reports from 14 companies listed on the IDX in 2017-2019. The sampling technique used purposive sampling and the data were analyzed using multiple linear regression analysis. Data were analyzed using SPSS version 20 software. The results showed that the profitability variable had a significant effect on stock prices with a significant value of 0.001 <0.05. Capital structure has a significant effect on stock prices with a significant value of 0.001 <0.05. And the results of the simultaneous test of profitability and capital structure have a simultaneous effect on stock prices with a significant value of 0.001 <0.05. In order to get better results, further research is expected to be able to add variables from financial ratios to profitability and capital structure as well as to increase research samples and extend the research period. Keywords: Profitability, Capital Structure, Stock Price